Immunogenicity and Safety of the M72/AS01E Candidate Vaccine Against Tuberculosis: A Meta-Analysis - Ji, Zhenhua; Jian, Miaomiao; Chen, Taigui; Luo, Lisha; Li, Lianbao; Dai, Xiting; Bai, Ruolan; Ding, Zhe; Bi, Yunfeng; Wen, Shiyuan; Zhou, Guozhong; Abi, Manzama-Esso; et al. (Frontiers in Immunology, 2019)
Background: Currently, there is no tuberculosis (TB) vaccine recommended for use in latent TB infections and healthy adults. M72/AS01E is a new peptide vaccine currently under development, which may improve protection against TB disease. This vaccine has been investigated in several phase I/II clinical trials. We conducted a meta-analysis to clarify the immunogenicity and safety of the M72/AS01E peptide vaccine. Methods: We searched the PubMed, Embase, and Cochrane Library databases for published studies (until December 2018) investigating this candidate vaccine. A meta-analysis was performed using the standard methods and procedures established by the Cochrane Collaboration. Results: Seven eligible studies – involving 4,590 participants – were selected. The analysis revealed a vaccine immunogenicity of 58.90%, significantly higher abundance of M72-specific CD4+ T cells (standardized mean difference [SMD]=2.58) in the vaccine group versus the control group, the highest seropositivity rate (74.87%) at 1 month after the second dose of vaccination (Day 60), and sustained elevated anti-M72 IgG geometric mean concentration at study end (Day 210) (SWD=4.94). Compared with the control, participants who received vaccination were at increased risk of local injection site redness (relative risk [RR]=5.99), local swelling (RR=7.57), malaise (RR=3.01), and fatigue (RR=3.17). However, they were not at increased risk of headache (RR=1.57), myalgia (RR=0.97), and pain (RR=3.02). Conclusion: The M72/AS01E vaccine against TB is safe and effective. Although the vaccine is associated with a mild adverse reaction, it is promising for the prevention of TB in healthy adults. Keywords: vaccine, tuberculosis, M72/AS01E, immunogenicity, safety